Pelatihan Microsoft Excel Di Kantor Badan Perencanaan Dan Penelitian Pengembangan Daerah Kota Padangsidempuan - Aris Munandar Harahap; Agustalinda Nora; Fithra Maharani; Nurdelila (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Nowadays, the rapid development of technology requires every individual to have the ability in the digital world. Digital skills are really needed in various aspects of humans today, especially the world of work. The world of work today relies a lot on digital technology in achieving its targets and goals. One of the skills that must be possessed by job seekers is the ability to use Microsoft Excel. Ms.Excel is a computer program used in making reports, presentations and performing simple analytical calculations commonly used in the world of work. Recognizing this as one of the contributions made by the university world is conducting training for institutions that need it. In this article, we will discuss the training of Ms. Excel which was carried out at the BAPLITBANGDA office in Padangsidimpuan City with the basics of Microsoft Excel. The purpose of this training is to improve the competence of the workforce in the Padangsidimpuan City BPLITBANGDA environment. The training activities use the drill system, which is a combination of theory and practice. In the practice session, participants work on the given exercises and mentoring is carried out to provide direction for participants. The evaluation was carried out at the end of the PkM implementation, from the statistical evaluation results showed that the training was able to improve the competence of participants in using Microsoft Excel and received positive responses from training participants with 62.78% giving a positive response.